Analysis Motivation Of Fighting Athletes Tarung Derajat Kaltim To Pon XX Papua - Didik Cahyono; Hamdiana; Muhammad Raihan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study was motivated by Tarung Derajat Kaltim athletes who passed the PON entry, the authors found that in self-preparation there were fewer interesting exercises due to the absence of training partners during self-training at home. This study aims to find out the motivation of PON athletes fighting degrees towards the XX PAPUA 2021   PON this study is intended to find out how much intrinsic and extrinsic motivation PON athletes fight kaltim degrees.  6 athletes using saturated sampling with a sample of 6 athletes. . The data collection in this study used non-test techniques using questionnaires and documentation to find out the motivation of  PON athletes fighting kaltim degrees.  Measurement scale  using Mahmud's likert scale (2011: 181) The results of the study using showed that the motivation of PON athletes fighting kaltim degrees is in the category either with the number of 4 athletes or 66.6%. Intrinsic Motivation pon athletes fighting the degree of Kaltim is in the good category with the number of 5 athletes 83.3%%. Extrinsic motivation of PON athletes fighting kaltim degrees is in the good category with the number of 4 athletes 66.6%